Zero Carbon Building Practices in Aotearoa New Zealand - Thao Thi Phuong Bui; Suzanne Wilkinson; Niluka Domingo; Casimir MacGregor (Energies, 2021)
In the light of climate change, the drive for zero carbon buildings is known as one response to reduce greenhouse gas emissions. Within New Zealand, research on climate change mitigation and environmental impacts of buildings has received renewed attention. However, there has been no detailed investigation of zero carbon building practices. This paper undertakes an exploratory study through the use of semi-structured interviews with government representatives and construction industry experts to examine how the New Zealand construction industry plans and implements zero carbon buildings. The results show that New Zealand’s construction industry is in the early stage of transiting to a net-zero carbon built environment. Key actions to date are focused on devising a way for the industry to develop and deliver zero carbon building projects. Central and local governments play a leading role in driving zero carbon initiatives. Leading construction firms intend to maximise the carbon reduction in building projects by developing a roadmap to achieve the carbon target by 2050 and rethinking the way of designing and constructing buildings. The research results provide an insight into the initial practices and policy implications for the uptake of zero carbon buildings in Aotearoa New Zealand.